Suppression of phagosome proteolysis and Matrigel migration with the α2-adrenergic receptor agonist dexmedetomidine in murine dendritic cells. (8th August 2013) - Ueshima, Hironobu; Inada, Takefumi; Shingu, Koh
Abstract: Dexmedetomidine is a highly-selective α2 -adrenergic receptor agonist used for sedation of critically ill patients in an intensive care setting. Dendritic cells (DCs) in peripheral tissues sense certain foreign antigens and ingest and process them, while migrating to the regional lymph node. Then, DCs present the processed antigen on their surface to stimulate the clonal proliferation of cognitive lymphocytes, leading to the establishment of adaptive immunity. In murine bone marrow-derived DCs, dexmedetomidine significantly delayed the intracellular proteolytic degradation of ovalbumin, while it did not affect phagocytosis, decreased the expression of the surface molecules I-A b and CD86, and suppressed cognitive helper T-cell proliferation. Furthermore, dexmedetomidine significantly suppressed DC migration both in vitro, using a Matrigel migration assay, and in vivo, using a foot pad-popliteal lymph node migration assay, which may be ascribed to the inhibition of type IV collagenase/gelatinase activity. Finally, vaccination with dexmedetomidine-treated DCs significantly suppressed the contact hypersensitivity reaction in vivo . These results indicate that dexmedetomidine may suppress immunity by inhibiting DC antigen processing/presentation and migration.